The Influence of Mood and Price Shop - Retno Wulansari (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of shop atmosphere and price on consumer buying interest in Hypermarket in Kota Tangerang Selatan. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study, the shop atmosphere has a significant effect on buying interest by 39.2%, hypothesis testing obtained t count> t table or (6,719> 1,994). Price has a significant effect on buying interest by 54.6%; hypothesis testing is obtained t count> t table or (9.173> 1.994). Shop atmosphere and prices simultaneously have a significant effect on buying interest with the regression equation Y = 8.676 + 0.254X1 + 0.543X2, and the contribution of the effect is 57.9%, hypothesis testing is obtained F count> F table or (47.424> 2.740).